2019
DOI: 10.3390/nano9010091
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Micelles for NIR/GSH-Triggered Chemophototherapy of Cancer

Abstract: The chemotherapy of stimuli-responsive drug delivery systems (SDDSs) is a promising method to enhance cancer treatment effects. However, the low efficiency of chemotherapy drugs and poor degradation partly limit the application of SDDSs. Herein, we report doxorubicin (DOX)-loading mixed micelles for biotin-targeting drug delivery and enhanced photothermal/photodynamic therapy (PTT/PDT). Glutathione (GSH)-responsive mixed micelles were prepared by a dialysis method, proportionally mixing polycaprolactone-disulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The micelles also exhibited good monodispersity, stability in the cell medium (~119.7 nm), low critical micelle concentration, good biodegradability, and resistance to photodecomposition. The designed biodegradable micelles showed promise as carriers for antitumor drug delivery and chemo/PTT/PDT combination therapy [83].…”
Section: Polymer Micellesmentioning
confidence: 99%
“…The micelles also exhibited good monodispersity, stability in the cell medium (~119.7 nm), low critical micelle concentration, good biodegradability, and resistance to photodecomposition. The designed biodegradable micelles showed promise as carriers for antitumor drug delivery and chemo/PTT/PDT combination therapy [83].…”
Section: Polymer Micellesmentioning
confidence: 99%
“…In addition to the importance of identifying new therapeutic targets, the development of novel Drug Delivery Systems (DDS) is a therapeutic strategy to pursuit to increase efficacy and reduce toxicity of well characterized molecules [1,2]. Several macromolecular structures are being explored as DDS [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al have explored the potential of PLA-PEG-AntiEGFR self-assemblies loaded with chlorin-e6 as a photosensitizer and found that this construct led to the increased internalization of the micelles through receptor-mediated endocytosis, which in turn led to increased cytotoxicity upon light activation [121]. Very recently, Zhang et al have exploited the highly selective interaction between avidin and biotin to specifically target cells overexpressing the biotin receptor [115].…”
Section: The Hydrophilic Blocksmentioning
confidence: 99%
“…For this purpose, PDT has been associated with multimodal imaging and other treatments such as chemotherapy or photothermal therapy (PTT). Doxorubicin or camptotecin, the most frequently used chemotherapeutic molecules, can be encapsulated [73,87,96,115] or chemically linked [80,90,93] to the polymer backbone and released under a precise stimulus. Chlorin-e6 [80], ICG [78], IR825 [80], IR 780 [106] or cypate [36,115] or pheophorbide [87] have been employed for the photothermal effect.…”
Section: High-performance Nanoassembliesmentioning
confidence: 99%